A formative and outcome evaluation of a community based antiretroviral therapy adherence programme : the case of Sizophila, Cape Town, South Africa - Mubekapi, Constance (Institute for Monitoring and Evaluation, 2015)
This dissertation is informed by a formative and outcome evaluation of the Sizophila programme, a community based antiretroviral therapy (ART) programme. The programme is administered by the Desmond Tutu HIV Foundation, a non-profit organization. The aim of the programme is to enhance ART health outcomes and promote individual wellbeing among people accessing human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) related services in the Hannan-Crusaid Centre. The goal of the evaluation was to assess the Sizophila programme implementation and to determine the impact of the home visit intervention on the medium-term outcomes of HIV viral load suppression and loss to follow-up. The evaluation was primarily for the programme staff. An implicit Sizophila programme theory was explicated from the programme staff and the evaluator reviewed relevant programme documentation to formulate an explicit programme theory. To assess the plausibility of this theory, social science perspectives based on reviews of empirical evidence of previous research were solicited. The initial Sizophila programme theory was simplistic in assuming a simple cause-effect relationship. The final programme theory recognised that programme interventions function through certain moderators and mediators that can either strengthen or weaken the intervention-outcome effect.